2017
DOI: 10.1017/cem.2017.414
|View full text |Cite
|
Sign up to set email alerts
|

A Web-based module and online video for pain management education for caregivers of children with fractures: A randomized controlled trial

Abstract: A web-based module and online video are superior to verbal instructions for improving caregiver knowledge on management of children's fracture pain without improvement in functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Although not specific to AOM, video discharge instructions provided to parents in the ED setting have consistently been associated with improved knowledge . In contrast, much fewer studies have explored the effectiveness of video discharge instructions on disease‐specific health outcomes and compliance . In our sample, recidivism and work/school/daycare absenteeism was uncommon.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although not specific to AOM, video discharge instructions provided to parents in the ED setting have consistently been associated with improved knowledge . In contrast, much fewer studies have explored the effectiveness of video discharge instructions on disease‐specific health outcomes and compliance . In our sample, recidivism and work/school/daycare absenteeism was uncommon.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, our sample was composed of a relatively educated group of parents where more than two‐thirds had a postsecondary degree and had previously cared for children with AOM. As a possible consequence, both groups scored below the STAI threshold for clinically significant situational anxiety and scored high on the postintervention knowledge questionnaire (Table ). We surmise that participants in both groups were quite capable, at baseline, of managing their child's symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research had identified deficits in function for children with fractures, 5,7 although few were informed by a qualitative lens. 17 Our findings can serve as source material for caregiver knowledge translation at the time of ED discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Specific topics derived from the literature included fracture pain, impact on sleep/school/play, and missed work for caregivers. 5,7,17 The interview guide is available in Supplemental text S1 (http://links.lww.com/PEC/A788). All questions were approved by the entire research team, including content and methods experts.…”
Section: Interview Guidementioning
confidence: 99%
See 1 more Smart Citation